Peculiarities of Integrating Mechanical Valves in Microfluidic Channels Using Direct Laser Writing - Lucero Hernandez-Cedillo; Deividas Andriukaitis; Lukas Šerpytis; Tomas Drevinskas; Olga Kornyšova; Vilma Kaškonienė; Mantas Stankevičius; Kristina Bimbiraitė-Survilienė; Audrius Sigitas Maruška; Linas Jonušauskas (Applied Bionics and Biomechanics)
Regenerative medicine is a fast expanding scientific topic. One of the main areas of development directions in this field is the usage of additive manufacturing to fabricate functional components that would be later integrated directly into the human body. One such structure could be a microfluidic valve which could replace its biological counterpart in veins as it is worn out over the lifetime of a patient. In this work, we explore the possibility to produce such a structure by using multiphoton polymerization (MPP). This technology allows the creation of 3D structures on a micro- and nanometric scale. In this work, the fabrication of microfluidic systems by direct laser writing was carried out. These devices consist of a 100 μm diameter channel and within it a 200 μm long three-dimensional one-way mechanical valve. The idea of this device is to have a single flow direction for a fluid. For testing purposes, the valve was integrated into a femtosecond laser-made glass microfluidic system. Such a system acts as a platform for testing such small and delicate devices. Measurements of the dimensions of the device within such a testing platform were taken and the repeatability of this process was analyzed. The capability to use it for flow direction control is measured. Possible implications to the field of regenerative medicine are discussed.